2016
DOI: 10.1371/journal.pone.0153256
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Gene Expression in the Murine Schwann Cell Lineage and the Acutely Injured Postnatal Nerve

Abstract: Schwann cells (SCs) arise from neural crest cells (NCCs) that first give rise to SC precursors (SCPs), followed by immature SCs, pro-myelinating SCs, and finally, non-myelinating or myelinating SCs. After nerve injury, mature SCs ‘de-differentiate’, downregulating their myelination program while transiently re-activating early glial lineage genes. To better understand molecular parallels between developing and de-differentiated SCs, we characterized the expression profiles of a panel of 12 transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 76 publications
5
50
0
Order By: Relevance
“…Rather, it appears that SCs, like CNS glia, produce Cxcl10 in an IFN-γ-independent fashion (47), because we found that Cxcl10 expression in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG localized to cell clusters expressing SC-associated genes. This finding is consistent with prior work showing that transient Raf hyperactivation in SCs can induce Cxcl10 expression (48,49). Consistent with Raf/Ras/MEK/ERK pathway signaling contributing to Cxcl10 expression in SCs, Cxcl10 expression was negatively correlated with Nf1 expression in the SC clusters and positively correlated with the expression of AP-1 transcription factors and of downstream targets induced by Ras signaling.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, it appears that SCs, like CNS glia, produce Cxcl10 in an IFN-γ-independent fashion (47), because we found that Cxcl10 expression in 2-month Dhh-Cre Nf1 fl/fl nerve/DRG localized to cell clusters expressing SC-associated genes. This finding is consistent with prior work showing that transient Raf hyperactivation in SCs can induce Cxcl10 expression (48,49). Consistent with Raf/Ras/MEK/ERK pathway signaling contributing to Cxcl10 expression in SCs, Cxcl10 expression was negatively correlated with Nf1 expression in the SC clusters and positively correlated with the expression of AP-1 transcription factors and of downstream targets induced by Ras signaling.…”
Section: Discussionsupporting
confidence: 91%
“…However, the expression of another immediate early gene, KROX24 , was highest in T-MSC-SCs. In accordance with that reported by other studies, KROX20 and KROX24 were expressed in a successive and mutually exclusive manner [32,33,34]. Krox20 promotes the differentiation of SCs to a myelinating phenotype while Krox24 is a non-myelinating SC marker [33].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with that reported by other studies, KROX20 and KROX24 were expressed in a successive and mutually exclusive manner [32,33,34]. Krox20 promotes the differentiation of SCs to a myelinating phenotype while Krox24 is a non-myelinating SC marker [33]. Krox20 and Krox24 are playing antagonistic roles during the development of the SC lineage [34].…”
Section: Discussionsupporting
confidence: 88%
“…The derepressed level of these transcription factors was not sufficient to drive significant levels of neuronal gene expression, however. A number of homeobox genes ( Hoxa7 , Hoxa10 , Hoxd1 3) and neural crest transcription factors ( Pax3, Tfap2a, Tfap2b ) that are expressed in early SC development (Balakrishnan et al 2016; Doddrell et al 2012) were also induced at a low level. Interestingly, a number of transcription factors involved in oligodendrocyte development ( Nkx6.2, Nkx6.1, Myrf ) were also somewhat elevated (Mitew et al 2013), but did not drive induction of unique oligodendrocyte genes (Lopez-Anido et al 2015) in the Eed cKO.…”
Section: Discussionmentioning
confidence: 99%